Postoperative hyperalgesia does not predict persistent post‐sternotomy pain; observational study based on clinical examination. Issue 4 (13th December 2015) - Setälä, P.; Kalliomäki, M.‐L.; Järvelä, K.; Huhtala, H.; Sisto, T.; Puolakka, P.
Abstract : Background: Persistent post‐sternotomy pain is a common problem, but the risk of developing it varies among patients. We sought to find out whether the risk of persistent post‐sternotomy pain could be predicted by measuring the area of acute sensory dysfunction around the sternotomy wound. The secondary aim was to determine risk factors for persistent post‐sternotomy pain. Patients and methods: Hundred patients who were scheduled to undergo elective coronary artery bypass surgery were recruited to the study. Patients were excluded if they had undergone previous cardiac surgery or if they lacked co‐operation. Preoperative pain scores were determined and the patients filled in questionnaires about depression, anxiety, and pain. The area of sensory dysfunction around the sternotomy wound was assessed by pin prick on postoperative day 4. The presence of persistent post‐sternotomy pain was determined at a follow‐up evaluation at 4–6 months after surgery. Results: The sizes of the area of hyperalgesia or overall sensory dysfunction were not associated with persistent post‐sternotomy pain. Independent risk factors for persistent post‐sternotomy pain were found to be smoking and high pain score on postoperative day 1. The prevalence of persistent post‐sternotomy pain in our study population was 38% analyzed by only the questionnaire and 15% according to the clinical examination. Conclusion: Measuring the area of hyperalgesia in the acute phase does not give any additional information on the risk of developing a persistent post‐sternotomy pain. We do thus not recommend measuring the area in this particular group of patients. Evaluation of pain by only a questionnaire risks to overestimate the presence of persistent post‐sternotomy pain as compared to clinical examination.